2015
DOI: 10.1177/1057567715574382
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Escalation in Reported Domestic Abuse

Abstract: Practitioners dealing with domestic abuse often claim that the problem escalates over time in both seriousness and frequency. We tested those claims on 36,000 police records of domestic abuse between 2009 and 2014 reported to Suffolk Constabulary in the east of England. Using the Cambridge Crime Harm Index as the measure of harm severity, we found no escalation in the majority of cases; 76% of all unique victim and offender units (dyads) had zero repeat calls. Among the cohort of 727 dyads who called police 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
75
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 11 publications
17
75
0
3
Order By: Relevance
“…Their profile of 692 perpetrators reported to the police for domestic abuse found that 50% were involved in an additional incident during the three-year follow-up period, and 18% of those that reoffended did so against a subsequent new partner. This is remarkably similar to the figure of 17% in another English police force area (Bland & Ariel, 2015). American research, using perpetrator samples derived from criminal justice rather than police data, has resulted in slightly higher prevalence rates of serial domestic abuse, ranging from 28% of probationers within a one-year period (Klein, Wilson, Crowe, & DeMichele, 2005) to 43% of persons arrested for violating a civil restraining order over a six-year period (Bocko, Cicchetti, Lempicki, & Powell, 2004).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Their profile of 692 perpetrators reported to the police for domestic abuse found that 50% were involved in an additional incident during the three-year follow-up period, and 18% of those that reoffended did so against a subsequent new partner. This is remarkably similar to the figure of 17% in another English police force area (Bland & Ariel, 2015). American research, using perpetrator samples derived from criminal justice rather than police data, has resulted in slightly higher prevalence rates of serial domestic abuse, ranging from 28% of probationers within a one-year period (Klein, Wilson, Crowe, & DeMichele, 2005) to 43% of persons arrested for violating a civil restraining order over a six-year period (Bocko, Cicchetti, Lempicki, & Powell, 2004).…”
Section: Introductionsupporting
confidence: 59%
“…One British study, relying upon police data, suggests that 80% of domestic abuse harm is attributable to less than 2% of victim-offender dyads (Bland & Ariel, 2015). As inferred by the current study, those that cause the most harm are likely to include some combination of serial, high-risk, and repeat domestic abusers.…”
Section: Resultsmentioning
confidence: 91%
“…That view was recently contradicted by evidence from the predominantly White European population of Suffolk County, UK (see Bland and Ariel 2015) that in domestic abuse police callouts escalation in severity is rare, as is escalation in frequency of calls, except among the most chronic cases. Yet in that analysis, the couples (or 'dyads' of victim and offender, defined here as unique opposite-sex intimate partners and ex-partners in a spousal, romantic or sexual relationship) included parent-child relationships, siblings and other kinds of family violence along with IPV.…”
Section: Introductionmentioning
confidence: 81%
“…Yet in that analysis, the couples (or 'dyads' of victim and offender, defined here as unique opposite-sex intimate partners and ex-partners in a spousal, romantic or sexual relationship) included parent-child relationships, siblings and other kinds of family violence along with IPV. The Bland and Ariel (2015) Suffolk police analysis also used observation periods that were not held constant, so that each dyad had different periods of time at risk for repeat incidents. While the Suffolk analysis was a major advance in the precision of evidence on domestic abuse, it leaves unanswered two key questions: whether the same conclusions would be reached if (1) dyads observed were restricted to intimate partners, and if (2) each dyad had an equal time period for further observation and recording of police contacts after the first case was reported to police.…”
Section: Introductionmentioning
confidence: 99%
“…It is ideally suited for comparing benefits of patrol time in practical terms, supplementing the more esoteric concept of Bstandardized mean differences^, which have little face value for public policy. For other applications of CHI in policing, see Bland and Ariel (2015).…”
Section: Dependent Variablesmentioning
confidence: 99%